Study on temporal-fuzzy fractional p-KdV equation with non-singular Mittag Leffler kernel - Kumar, Ajay; Meher, Ramakanta (Mathematical Modelling and Analysis, 2024)
This work discusses the solution of temporal-fuzzy fractional non-linear p-KdV equations employing a singular kernel and a non-singular Mittag Leffler kernel. A novel q-homotopy analysis approach with a generalised transform is proposed to study the fuzzy time-fractional model with two distinct fractional operators, and the behaviour of the solution is studied in both crisp and uncertain cases. Consequently, the efficiency and accuracy of the proposed method have been obtained by comparing the obtained numerical results with the available results under the assumption of crisp case for α = 1 that validate the obtained results. Finally, the efficiency of the proposed fractional orders is checked with distinct fractional operators.